German electricity prices: Only modest increase due to renewable energy expected - Thure Traber; Claudia Kemfert; Jochen Diekmann (Weekly Report, 2011)
Consumer prices for electricity in Germany have risen considerably in recent years. These price increases are partially attributable to a strong rise in the apportionment for the promotion of renewable electricity in accordance with the German Renewable Energy Sources Act (EEG). The EEG apportionment and associated VAT currently account for approximately one-sixth of household spending on electricity. Yet the increasing generation of power from renewables leads to decreased wholesale electricity prices. As a result, the net burden on the consumer - given effective competition - is lower than the apportionment. According to modelling calculations performed by the German Institute for Economic Research (DIW), inflation-adjusted wholesale prices for electricity will only increase by 11% between 2010 and 2020 to 4.9 euro cents per kilowatt-hour (kWh), despite increasing fuel and CO2 certificate prices. In the absence of expanded deployment of renewable energy, a higher price increase of 20% can be expected. Although electricity generation from renewable sources is forecasted to more than double by 2020, the EEG apportionment borne by consumers will in real terms only be 3.64 euro cents per kWh, and thus only slightly higher than it is today. The main reason for this low growth is the fact that the tariffs for new installations are digressive, falling year by year. In addition, tariffs are diminished in real terms by price inflation. Our modelling calculations assume that legislators will take action against the recent overinvestment in the solar electricity sector. Thanks to a significant fall in the cost of photovoltaic (PV) systems, the reduction of PV tariffs can be placed on an accelerated timetable. Over the long term, the overall level of support provided under the EEG should be reduced. For the further deployment of renewable energy it is necessary to expand Germany's power grid in addition to the availability of energy storage facilities. Steps must also be taken to increase competition in electricity markets.
Keywords: D4; Q2; Q4; 330; electricity markets; renewable energy; energy policy